Challenges in blending quality with morality in medical profession - Quddus, S. M. Abdul (2019)
A ‘profession’ largely refers to an occupation with secured tenure and that carries substantial honour with a scope for fulfilling social roles and obligation, with rewards and higher social prestige attached to it in addition to access to authority and power (Kocka, 1985; Burrage et al 1990). However, the practice of a ‘profession’ like medicine presupposes specialized and scholarly training, competence and a particular code of professional ethics such as continuously improving quality and standards of practice (ibid). Hargreaves argues that high quality training and competence facilitate a practitioners’ confidence and their quality service delivery lead to improved professional status and increased public trust (Hargreaves, 2000). It is relevant to mention that the entire planet could now be considered to be under the control of one economic order that is capitalism. Capitalism appeals to relentless competition in the pursuit of profits, personal gain and individual satisfaction. Therefore, many professional occupations have acquired a new environment and new conditions necessary for their continued legitimacy, social recognition and prestige. The direction of professional work today is economically inspired and reflects the material interests of practitioners such as is the case with medical doctors (Freidson, 2001). Hence, major professions (e. g. medical, law, accounting, etc) have suffered some loss of public confidence and trust, and many of them have come under pressure to reduce the costs of their services to clients and the state (ibid, p.193). Critics deplore instances of unethical behaviour, such as the exploitation of patients, dishonesty in the workplace, fraud, manslaughter, and other crimes familiar to all of us (see Wolinsky and Brune, 1994 and Rodwin 1993 for American Medicine). Therefore, in order to sustain professional legitimacy and public trust it is essential that medical professionals not use their expert knowledge for selfish advantage but rather put an emphasis on the ethical and moral aspects relevant to their professional practice. Thus there is a demand for a new professionalism concerning the discourse on the change of behaviour on the individual and organizational levels of ‘professions’ in blending quality with ethics and morality. The purpose of my paper/ presentation will therefore be to discuss the relationship between professionalism, quality and morality and to outline some conditions for a new professionalism as a means to providing quality and morality in the professional practice of the medical profession.